Reasoning of the expediency of using vibration supports with variable parameters - Sheka, Oleksandr; Yakovenko, Andrii; Vedmid, Vasyl (Academic journal. Industrial Machine, Building Civil Engineering, 2022)
The problem of reducing the negative impact of vibration on staff and equipment and their compliance with sanitary standards is always relevant for construction vibrating machines with vibration exciters of various types and modes. So, in practice, vibration isolation of vibroactive elements of vibrating machines and technological equipment is applied using systems with quasi-zero stiffness. This article highlights the results of experimental studies of changes in the elastic qualities of vibration support parameters at different pressure levels and changes in the length of the free part of the elastic element. Therefore, the construction of a vibration support with a limiter of the free part of the elastic element was developed. The stiffness of the support changes as a result of changing the free part of the support with metal limiters. The results of the search experiment showed that the deformation of the rubber element is carried out according to a law close to the linear one. Therefore, a mathematical model in the form of regression was built to conduct the main experiment and process the obtained data. The obtained regression equation makes it possible to establish the dependence of the shrinkage of the support when the pressure on it changes and the height of the free part of the elastic element.